Does rotational thromboelastometry accurately predict coagulation status in patients with lupus anticoagulant?. (13th May 2018) - Hensch, L.; Kostousov, V.; Bruzdoski, K.; Losos, M.; Pereira, M.; de Guzman, M.; Hui, S.; Teruya, J.
Abstract: Introduction: Rotational thromboelastometry (ROTEM) is increasingly used as a tool for monitoring coagulation status. However, ROTEM is susceptible to misinterpretation due to particular coagulation abnormalities. Here, we report the effects of lupus anticoagulant (LA) on ROTEM. Methods: A prospective observational analysis was performed on 16 children with prior studies indicating the presence of LA or antiphospholipid antibodies. ROTEM analysis was performed, and samples were further analyzed by adding phospholipids (PL) to repeat ROTEM analysis if clotting time (CT) abnormalities were discovered with comparison to ROTEM using an equal volume of isotonic saline. Prothrombin time (PT), activated partial thromboplastin time (APTT), dilute Russell's viper venom test (DRVVT), hexagonal phase phospholipid neutralization test (StaClot LA), and factor II activity studies were additionally performed. Results: Eighteen samples were analyzed by ROTEM. Prolonged CT on INTEM and EXTEM was observed for 11 samples. Samples with CT prolongation had high DRVVT ratios and prolonged APTT. Further, the addition of PL partially reversed this effect, demonstrating PL‐dependent inhibition as the cause of CT prolongation. No factor II deficiencies were identified, excluding LA hypoprothrombinemia syndrome as a cause of these findings. Conclusion: Strongly positive LA can prolong the CT on ROTEM studies and lead to erroneous conclusions regarding coagulation status in this patient population.